Impacto do contexto de trabalho e da resiliência sobre o bem-estar no trabalho de profissionais dos Centros de Atenção Psicossocial - Alves, Haiana Maria de Carvalho (2015)
Well-being at work has been regarded as a psychological construct brought about by positive links with work and with the organization. This investigation, which approached the impact of working context and resilience on the well-being of the Psycho-Social Attention Center (CAPS) Professionals from two Brazilian cities aimed to add findings to the area s knowledge. The CAPS are public services replacing the asylum model for the treatment of people suffering from psychic problems, backed up by and with foundations on the National Policy for Mental Health (PNSM). The theoretical conception used in this work, by its turn, approaches resilience at work as a positive psychological state related to the performance at work even in complex, wearing-out situations. Regarding working context evaluation, it was considered that it is depicted as a subjective interpretation of the professionals about the working conditions, the organization of work, and the social-professional relationship. 81 professionals from the CAPS of cities Petrolina PE and São Bernardo do Campo SP, 37 years old on average (DP = 10.45), mostly female in sex (65.4por cento) with schooling above college degree and complete post-graduation (both 29%), who declared to be married or at stable unity (39%). In this study, well-being at work was considered as the criterion variable, and resilience at work and working conditions, as predictors. A quiz was applied to collect the participants social-demographic data and three valid Brazilian scales, being: Well-being-at-work Inventory (IBET-13), Resilience-at-Work Scale (ERT), and Work Context Evaluation Scale (EACT). Statistical, exploratory, and descriptive analysis were carried out, as well as regression analysis, and variance analyses (ANOVA) to describe participants, variables, and test the model. The results partly backed up the prediction model, for the social-professional factor confirmed itself as significant predictor for Well-Being at Work, when there was no significant prediction from the other variables (Working Conditions, Working Organization, and Resilience at Work). These data can reveal that good social-professional relationships tend to increase the satisfaction level and affective organizational commitment with the institution, as well as the increase in the engagement level of these professionals with their work.